Fear of Recurrence and Somatic Symptom Severity in Multiple Myeloma Patients: An Institution-Based Cross-Sectional Study - Shenoy V P, Praveen Kumar; Raghavan, Vineetha; Manuprasad, Avaronnan; B., Sajeev Kumar P.; Raj, Zoheb; Nair, Chandran K. (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Psychosocial concerns especially fear of cancer recurrence (FCR) is less commonly addressed among patients with multiple myeloma in India. Myeloma being incurable, an understanding of this problem is essential for adequately addressing them.Objectives To study the prevalence of FCR among patients with multiple myeloma and determine the prevalence of somatic symptoms among patients with multiple myeloma.Materials and Methods A cross-sectional study was performed at our institution among patients with multiple myeloma who had been on treatment for 1 year or more. The study was conducted between July 01 and July 31, 2015. At least 49 patients were required to be recruited into this study to meet its first objective. Patients were administered fear of cancer recurrence inventory (FCRI) questionnaire and Physical Health Questionnaire-15 (PHQ-15) questionnaire.Results Sixty-four patients participated in the study. The median age was 60 years (34–80 years) and majority were females (N = 38, 60%). ISS staging information was available in 53 (83%) patients. Of 53, 24 (45%) were ISS stage 3, 12 (23%) were ISS stage 2 and remaining stage 1. The mean total FCRI score in the study population was 27.95 (SD: 24.5). Moderate to high levels of FCR were seen in 40% (N = 26). Using PHQ-15, 54 (84%) patients had mild or lesser somatic symptom burden. Disease status of patients at the time of this study had a significant statistical association with PHQ-15 scores (mean score in partial response (PR) or more group 6.02 versus 8.00 in less than PR group, p = 0.02).Conclusions Overall, FCR scores and somatic symptom severity were low among our patients with multiple myeloma. However, a significant proportion had moderate to high levels of FCR. Further studies involving larger numbers in a prospective manner required to confirm our findings of fear of cancer recurrence among patients with multiple myeloma.
Keywords: fear of recurrence; multiple myeloma; PHQ-15; FCRI